Hollywood left and right : how movie stars shaped American politics - Ross, Steven Joseph (New York, NY : Oxford University Press, 2011)
From the publisher. In Hollywood Left and Right, Steven J. Ross tells a story that has escaped public attention: the emergence of Hollywood as a vital center of political life and the important role that movie stars have played in shaping the course of American politics. Ever since the film industry relocated to Hollywood early in the twentieth century, it has had an outsized influence on American politics. Through compelling larger-than-life figures in American cinema -- Charlie Chaplin, Louis B. Mayer, Edward G. Robinson, George Murphy, Ronald Reagan, Harry Belafonte, Jane Fonda, Charlton Heston, Warren Beatty, and Arnold Schwarzenegger -- Hollywood Left and Right reveals how the film industry's engagement in politics has been longer, deeper, and more varied than most people would imagine. As shown in alternating chapters, the Left and the Right each gained ascendancy in Tinseltown at different times. From Chaplin, whose movies almost always displayed his leftist convictions, to Schwarzenegger's nearly seamless transition from action blockbusters to the California governor's mansion, Steven J. Ross traces the intersection of Hollywood and political activism from the early twentieth century to the present. Hollywood Left and Right challenges the commonly held belief that Hollywood has always been a bastion of liberalism. The real story, as Ross shows in this passionate and entertaining work, is far more complicated. First, Hollywood has a longer history of conservatism than liberalism. Second, and most surprising, while the Hollywood Left was usually more vocal and visible, the Right had a greater impact on American political life, capturing a senate seat (Murphy), a governorship (Schwarzenegger), and the ultimate achievement, the Presidency (Reagan).
Introduction: movie stars and politics -- The first political movie star: Charlie Chaplin -- The man who brought Hollywood into the Republican Party: Louis B. Mayer -- Little Caesar and the HUAC mob: Edward G. Robinson -- Hollywood and the conservative revolution: George Murphy and Ronald Reagan -- Politics in black and white: Harry Belafonte -- Movement leader, grassroots builder: Jane Fonda -- Moses and the red tide: Charlton Heston -- President Bulworth, or, will Mr. Beatty go to Washington?: Warren Beatty -- Governor Arnold and the age of celebrity politics: Arnold Schwarzenegger -- Epilogue.
Includes bibliographical references and index.
Keywords: United States -- Politics and government -- 20th century; Motion picture industry -- United States -- Influence; Motion picture producers and directors -- Political activity -- United States -- History -- 20th century; Motion picture actors and actresses -- Political activity -- United States -- History -- 20th century